Factors Influencing the Management of Penggaron Terminal Facilities Based On Importance Performance Analysis (IPA) Method Results - Navis, Ahmad Akbar; Rizani, Mohammad Debby; Yudaningrum, Farida (Science and Technology Research Centre, Universitas PGRI Semarang, 2024)
Penggaron Terminal is a type B terminal located in Pedurungan District which serves majors in the cities of Central Java Province. This study aims to determine the factors that influence the management of facilities at Penggaron Terminal. This research was conducted at the Penggaron terminal for two weeks, Questionnaires were distributed on Mondays and Sundays, in the morning at 07:00-10:00 WIB and in the afternoon at 16:00-18:00 WIB. This research is included in the quantitative research. Data collection uses primary data, namely data obtained from respondents' answers. Secondary data in the form of literature as a support related to research. Based on the data analysis, the results of the factors that influence the management of facilities at Penggaron Terminal are the availability of main and supporting facilities. Meanwhile, facilities that are not yet available at Penggaron Terminal are green open spaces and storage areas for goods.Keywords: service level, user, Penggaron Terminal.